203 Developing and Fine-Tuning Novel 3D-Printed Biodegradable Scaffolds to Promote Auricular Cartilaginous Regeneration for Surgical Implantation. (4th May 2021) - Srivastava, A; Long, E; Wu, L; Song, W H
Abstract: Introduction: Microtia, a congenital cartilaginous defect, poses major challenges in cosmetic surgery. Biodegradable polymers promote chondrogenesis, with promises of seeding cells into synthetic-polymer-implants for surgical fixation. However, existing polymers used in auricular reconstruction present limitations including inflammation, fibrosis, and extrusion. This study aimed to modulate the mechanical properties of the novel polylactic-acid/polyhydroxyalkanoate (PLA/PHA) blend by 3D-printing and hence, evaluate its suitability to the auricular microenvironment in developing next-generation reconstructs. Method: Digitally defined PLA/PHA scaffolds were free-form 3D-printed at various infill densities and thicknesses. Through tensile testing, tensile moduli, yield point, maximum strength, tensile toughness, and stiffness were calculated, alongside Finite Element Analysis (FEA) and contact angle tests. Finally, preliminary cell seeding was conducted. Results: Increasing infill densities of PLA/PHA scaffolds from 30%-60% significantly increased tensile moduli, yield point and maximum strength (P < 0.01). Tensile stiffness increased significantly with scaffold thicknesses between 1mm-2mm (P < 0.05). Cell studies showed promising proliferative activity. Conclusions: The mechanical properties and structural stiffness of 3D-printed PLA/PHA scaffolds can be significantly tailored by altering infill density and thickness, respectively. The digitally defined interconnected pores within printed PLA/PHA scaffolds reduce stiffness mismatches between surgical-synthetic polymers and auricular cartilage, potentially promoting cell migration and nutrition transportation in future reconstructs.